2021
DOI: 10.1080/09581596.2021.1970720
|View full text |Cite
|
Sign up to set email alerts
|

Public health morality, sex, and COVID-19: sexual minority men’s HIV pre-exposure prophylaxis (PrEP) decision-making during Ontario’s first COVID-19 lockdown

Abstract: Experts have warned that COVID-19 control measures may amplify health inequities among gay, bisexual, queer, and other men who have sex with men (GBM). For HIV-negative GBM, concerns have been raised as to how COVID-19 will disrupt access to HIV pre-exposure prophylaxis (PrEP). Our study offers empirical findings on these issues, drawing on in-depth interviews conducted with 25 HIV-negative GBM living in Ontario, Canada during the first wave of the COVID-19 pandemic. Our thematic analysis draws from the sociol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Participants were asked about their specific sexual practices and PrEP experiences, and any changes they were observing within the GBQM community because of PrEP. We also discussed the impact of COVID-19 lockdown procedures on sexual practices and PrEP use, which are reported on elsewhere ( Gaspar et al 2022 ). A web site and poster were used to recruit PrEP users and non-PrEP users.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were asked about their specific sexual practices and PrEP experiences, and any changes they were observing within the GBQM community because of PrEP. We also discussed the impact of COVID-19 lockdown procedures on sexual practices and PrEP use, which are reported on elsewhere ( Gaspar et al 2022 ). A web site and poster were used to recruit PrEP users and non-PrEP users.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual risk-taking is rarely static and a GBQM’s need for PrEP is likely to change over time. For example, based on data collected as part of the current study, we previously reported on how many GBQM in Ontario stopped and restarted their PrEP use in response to shifting COVID-19 control measures that affected their ability to have sex with casual or new partners ( Gaspar et al, 2022 ). Newman et al’s (2018) analysis is influenced by research on HIV and GBQM which acknowledges that people do not always “behave” the way health promotion models would predict.…”
Section: Sexuality In and Through The Cascadementioning
confidence: 99%
See 1 more Smart Citation
“…Theme 2: Loss of Social and Kinship Connection. The loss of social and kinship connection was reported across eight articles (Braksmajer & London, 2021;Gaspar et al, 2021;O'Brien et al, 2021;Pereira et al, 2021;Philpot et al, 2021;Quinn et al, 2021;Riggle et al, 2021;Westwood et al, 2021). This type of loss largely related to losses in the quality and quantity of friendships, LGBTQ+ people's Family of Choice, their Family of Origin and romantic or sexual partners (Wheat & Thacker, 2019).…”
Section: Inductive Thematic Synthesismentioning
confidence: 99%
“…Furthermore, observational research demonstrates that GBQM take PrEP when they feel that they need it, others avoid taking PrEP if they do not perceive a benefit over their current safer sex practices, and many discontinue PrEP if they feel that their risk for HIV has lowered substantially (Newman et al, 2018). For instance, many GBQM stopped taking PrEP when COVID-19 protocols prohibited them from having casual sex (Gaspar et al, 2022a). GBQM do not tend to use PrEP in a cavalier fashion.…”
mentioning
confidence: 99%